The canning quality of Philippine oranges (Ladu and King varieties) - Peleo, Teresita Ochoa 1940- ([Quezon City], 1961)
The possibility of canning native varieties of orange, Ladu and King is determined with a view of determining their canning qualities. The study notes that with different varieties of orange, slightly different treatments are necessary in order for the canning quality to be generally acceptable.
Literature cited: l. 36-37.
Thesis (B.S. Food Tech.)--University of the Philippines.
Keywords: Orange, Canned